Peer effects and school design: An analysis of efficiency and equity - Lionel Perini (University of Neuchâtel, Institute of Economic Research (IRENE), 2012)
This paper estimates educational peer effects at the lower secondary level in Switzerland where different tracking systems coexist. Using a cross-sectional survey based on standardized questionnaires, the structure and magnitude of social interactions among classmates are analyzed. The results are used to find out if grouping students in a completely non-selective way could increase efficiency and equality of opportunity. Empirical findings suggest that mixing students in reading and science classes could enhance efficiency and equity while a similar practice in mathematics courses could only improve equity without any gain in efficiency.
Keywords: I21; J24; 330; Peer effects; ability tracking; family background; equality of opportunity; quantile regression